The effect of local reinforcing bar reductions and anchorage zone cracking on the load capacity of RC half-joints. (1st December 2017) - Desnerck, Pieter; Lees, Janet M.; Morley, Chris T.
Highlights: Nine different reinforced concrete half-joint scenarios are tested. For studied specimens the impact of the concrete strength was negligible. A local reduction at the inner nib resulted in a 35% reduction in failure load. Two methods for mimicking corrosion cracking of concrete were implemented. Whereas individual deficiencies had little effect, synergistic effects were noted. Abstract: Half-joint beams, also referred to as dapped-end beams, have been the subject of several studies, primarily focussing on the design optimisation of new reinforced concrete beams and bridge decks. Existing half-joint structures, however, often show signs of deterioration and can exhibit improper reinforcement detailing. In order to gain a better insight into the impact of local corrosion, anchorage cracking, limited amounts of provided shear reinforcement, and improper reinforcement detailing, a test program was designed. Full-scale tests on nine half-joint beams were performed. The results of the study show that even though the impact of an individual shortcoming on the load carrying capacity of reinforced concrete half-joint beams might not be substantial, inspectors and assessors should pay attention to the possibility of combined effects. When multiple deterioration processes are noted and/or questions are raised with respect to the reinforcement detailing, the impact on the load carrying capacity of the beam might be larger than the linear combination of the individual effects.